Multi-Rotor Wake Interaction Characterization - Gregorio, F. De; Rossignol, K.-S.; Ceglia, G.; Yin, J. (My University, 2023)
The paper presents part of the experimental activities carried out in the GARTEUR Action Group HC/AG-26 to study the acoustic and aerodynamic characteristics of small rotor configurations, including the influence of the rotor-rotor interactions. Two rotors equipped with two-bladed propellers with a diameter of D=165.1mm were used at two different rotating speeds of 8025 RPM and 10120 RPM and different geometry configurations. Isolated rotor and coaxial configurations in hover conditions were assessed. The rotor slipstream characterization, in terms of aerodynamic loads, flow field velocity and acoustics emissions, was performed using a six-component load cell, Particle Image Velocimetry and microphone array measurements. The effect of the rotor support/fairing on the performance of the isolated rotor was investigated together with the rotor-rotor interaction for the coaxial configuration at two rotor distances of ?z = 0.5R and ?z = 1.0 R. The results indicated an effect of the support/fairing on the propeller performance, a loss of thrust of the lower rotor and a higher noise emission for the coaxial configuration characterized by the larger rotor distance. The turbulent kinetic energy and the meandering of the blade tip vortices sustained the acoustics results.
Keywords: Aerodynamics